(untitled) (Italian Journal of Public Health, 2010)
Background: The data-collection form used for Italy’s recently established national HIV surveillance system does not include sufficient information to thoroughly describe the dynamics of the epidemic. In addition, comparisons with data from other European countries are difficult. To address this issue, we have developed a more detailed form based on forms used in other European countries. Methods: Data-collection forms used in other countries were evaluated, and the information collected was categorised by topic. Based on this evaluation, a form was developed for use in Italy. Results: The forms used in other countries are more detailed than the Italian form, and we propose adding the following information to the Italian form: i) the year of entry in Italy for non-nationals; ii) testing pattern (i.e., the number of tests in the previous two years and during lifetime); iii) whether or not infection was recent, based on the antibody avidity index, and which test and cut-off were used; iv) whether or not testing was performed in the acute phase of infection, based on symptoms; and v) a checklist of reasons for undergoing testing. We also added a “Comments” section for information not recorded elsewhere on the form. Discussion: The more detailed form will allow for a more thorough description of the characteristics of newly infected persons and of the dynamics of the epidemic in Italy, which is fundamental for prevention and control initiatives. It will also allow for comparisons to be made against data from other European countries, revealing important similarities and differences.